Complex Multimeric [FeFe] Hydrogenases: Biochemistry, Physiology and New Opportunities for the Hydrogen Economy - Schuchmann, Kai; Chowdhury, Nilanjan Pal; Müller, Volker (Frontiers in Microbiology, 2018)
Hydrogenases are key enzymes of the energy metabolism of many microorganisms. Especially in anoxic habitats where molecular hydrogen (H2) is an important intermediate, these enzymes are used to expel excess reducing power by reducing protons or they are used for the oxidation of H2 as energy and electron source. Despite the fact that hydrogenases catalyze the simplest chemical reaction of reducing two protons with two electrons it turned out that they are often parts of multimeric enzyme complexes catalyzing complex chemical reactions with a multitude of functions in the metabolism. Recent findings revealed multimeric hydrogenases with so far unknown functions particularly in bacteria from the class Clostridia. The discovery of [FeFe] hydrogenases coupled to electron bifurcating subunits solved the enigma of how the otherwise highly endergonic reduction of the electron carrier ferredoxin can be carried out and how H2 production from NADH is possible. Complexes of [FeFe] hydrogenases with formate dehydrogenases revealed a novel enzymatic coupling of the two electron carriers H2 and formate. These novel hydrogenase enzyme complex could also contribute to biotechnological H2 production and H2 storage, both processes essential for an envisaged economy based on H2 as energy carrier.